Ischemic Stroke and Ruptured Mycotic Aneurysm, Two Complications of Infective Endocarditis in One Patient - Alassane Mamadou Diop; Ahmadou Bamba Mbodj; Serigne Abdou Aziz Fall; Ibrahima Niang (Case Reports in Neurological Medicine)
The incidence of infective endocarditis is estimated to be around 30 cases per million inhabitants/year. It can be responsible for various neurological complications such as cerebral infarction, meningitis, cerebral abscesses, and cerebral hemorrhage due to ruptured mycotic aneurysms. Several germs have been incriminated in this condition including Staphylococcus, Streptococcus, and Enterococcus. We report the case of a 64-year-old patient who presented with an acute motor deficit of the left upper limb associated with dysarthria. MRI showed infarcts in both cerebral hemispheres, and the TOF sequence showed an amputation of M2. On transesophageal ultrasound, there was evidence of vegetations at the mitral valve. Blood culture isolated Streptococcus oralis. With antibiotic treatment, the evolution was marked by a stable apyrexia with regression of the dysarthria. Before her surgery, she suddenly developed aphasia with worsening of the motor deficit. CT scan showed a right fronto-parietal hematoma which was related to a ruptured cerebral aneurysm. She underwent endovascular embolisation and subsequent cardiac surgery.